The Innovated Laser Assisted Flapless Corticotomy to Enhance Orthodontic Tooth Movement - Seifi, Massoud; Younessian, Farnaz; Ameli, Nazila (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Corticotomy-facilitated orthodontics provides a means for rapidly moving teeth purportedly with little damaging effects to the periodontium and with greatly reduced treatment time. The aim of this study was to enhance the orthodontic tooth movement by reducing the cortical bone layer (resistant to bone re-sorption relative to spongious bone) following Erbium, Chromium doped Yttrium Scandium Gallium Garnet (Er-Cr: YSGG)laser irradiation, without reflection of surgical soft tissue flap. METHODS: In the present experimental study, 8 New Zealand Male rabbits were the samples for the research. The right first premolar of each rabbit (experiment group) underwent treatment for mesial movement with 75 gram of orthodontic force by using closed Ni-Ti coil spring (Dentaurum®). Coil spring was fixed in the cervical region of first premolars by means of ligature wire and No-Mix composite (Dentaurum®) and also activated to the cervical site of incisors. The left first premolars of the subjects were considered as the control group. Laser corticotomy was performed in anesthetized rabbits. Samples were sacrificed for determination of tooth movement after initiating premolar protraction on the 21th day. The amount of orthodontic tooth movement was assessed by using a metal feeler gauge with the precision of 0.01 mm, between mesial surface of the second premolars and distal surfaces of the first premolars. The statistical package of SPSS (Kolmogorov - Smirnov and ANOVA test) was used for analytical evaluation of the measurements. RESULTS: The amount of orthodontic tooth movement in the experimental group (mean=1.653±0.34 mm) was significantly (p<0.001) greater than that of the control group (mean=0.936 ±0.28 mm). The innovated laser assisted corticotomies enhanced the rate of orthodontic tooth movement on the intervention side, significantly (p<0.001). CONCLUSION: The innovated method of laser assisted flapless corticotomy is a useful procedure for reducing treatment time and damage to periodontium. It also eliminates the necessity of more invasive intervention of flap surgery.